A research on the performance of down-flow hanging sponge (DHS) reactor treating domestic wastewater - Nguyen Trung Hiep; Le Thi Hong Tuyet; Dinh Thi Nga; Phan Dinh Tuan (Vietnam Journal of Science and Technology, 2018)
The aim of this study was to evaluate the performance of a down-flow hanging sponge (DHS) system in treating domestic wastewater. A pilot-scale of DHS system with a capacity of 60 L was designed and fabricated from polyvinyl chloride (PVC). The dimensions of DHS system are 1.5 m in height and square surface with 0.2 m in width, consists of three identical segments connected vertically in series. Each segment was filled by polyurethane sphere containing sponge. The total area of sponge and polyurethane sphere was 3,300 m2 m-3, density at 150 kg m-3, void ratio at 90%. DHS system was operated at ambient temperature within 82 days and stepwise increased of organic f rate from 0.5 to 1 and 1.5 kg COD m-3 d-1. The results showed that, this system performed well throughout the operational period and achieve the maximum removal of COD, BOD5, NH4+-N, and TN as 80%, 83%, 65% and 60%. The effluent of wastewater from DHS system achieved the requirement for National technical regulation on domestic wastewater of Vietnam type B QCVN 14:2008/BTNMT. In conclusion, the performance of DHS system indicated a high potential for application in removing organic matter and converting nitrogen ammonia to nitrogen nitrate, however it did not perform well for the removal of total nitrogen, it is necessary to study further by providing an anoxic zone in the system to enhance the treatment of nutrient in wastewater.